UF-T3 and UF-T4: Two Sterile Lantana camara Varieties - Zhanao Deng; David M. Czarnecki; Sandra B. Wilson; Gary W. Knox; Rosanna Freyre (EDIS, 2012)
Lantana camara plants are valued for their bright flower color, butterfly attraction, tolerance to harsh environmental conditions, low maintenance requirements, and ease of propagation and production. But many existing varieties can be weedy or invasive when grown in tropical and subtropical regions. So, in 2004, UF/IFAS started a program to develop sterile L. camara varieties with little to no invasive potential. This 8-page fact sheet introduces the recently released UF-T3 and UF-T4 lantana varieties that have resulted from these breeding, selection, and testing efforts. Written by Zhanao Deng, David M. Czarnecki II, Sandra B. Wilson, Gary W. Knox, and Rosanna Freyre, and published by the UF Department of Environmental Horticulture, August 2012.